{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

第3章(1)

第3ç«&n...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: * 1· ª 3 à * ª · ªs 3.1 Lª TI i6 * ·’ * ª · ’ i6 LTI ôÀ s h(t )s x(t ) = ª e· s’ 0ti6 * ª · ’ i6 y zs (t )s ∞ y zs (t ) = x(t ) * h(t ) = ∫ x(t − τ )h(τ )dτ −∞ ∞ =∫ e s0 ( t −τ ) −∞ ∞ h(τ )dτ = e H ( s0 ) = ∫ h(τ )e − s0τ dτ −∞ *ª·x ’ 6* ä o 3 u á s0 t ∫ ∞ −∞ h(τ )e − s0τ dτ y (t ) = H ( s0 )e s0t 3ª Y · TI À E L Ðü l * [email protected] 1 * 1· ª 3 à * ª · ªs h(t ) = e −2t u (t ) M ð LTI (1) x1 (t ) = e − t y (2) x2 (t ) = e − t u (t ) ∞ H ( s0 ) = ∫ h(τ )e − s0τ −∞ ∞ ∞ dτ = ∫ e − 2τ u (τ )e − s0τ dτ −∞ = ∫ e −( s0 + 2 )τ dτ = 0 (1) x1 (t ) = e − t ( s0 = −1) (3) x3 (t ) = 1 + cos(t ) − ( s0 + 2 )τ 0 e s0 + 2 ∞ 1 = s0 + 2 y1 (t ) = H ( s0 ) s 0 Re( s0 ) > −2 e −t = e −t = −1 (2) x2 (t ) = e − t u (t ) y2 (t ) = x2 (t ) * h(t ) = e − t u (t ) * e −2t u (t ) = (e − t − e −2t )u (t ) [email protected] 2 * 1· ª 3 à * ª · ªs - ( ) 1 jt (3) x3 (t ) = 1 + cos(t ) = e + e + e − jt 2 1 0⋅t y3 (t ) = H (0)e + H ( j1)e jt + H (− j1)e − jt 2 0⋅t [ 1 1 e jt e − jt 1 2 cos(t ) + sin(t ) =+ + = 2+ 5 2 2 2 + j 2 − j 3Y 3.2ª · ( E Ð * ˜Á 3.2.1 s x(t ) FS s À FS s ÀÐ Ts [email protected] x(t ) = x(t + T)s 3 * 1· ª 3 à * ª · ªs x(tª ) · š ξ x(t ) = ∞ ∑a ϕ k =− ∞ k 1 ak (k = 0,±1,±2, ) k k =− ∞ k 2π ω0 = T x(tª ) · š ξ a±1ϕ ±1 (t ) = a±1e ± jω 0t x(tª ) · š ξ a± 2ϕ ± 2 (t ) = a± 2 e ± j 2ω 0t a0 ∑a e jkω 0t x* (tª ) · š ξ 2 a0ϕ 0 (t ) = a0 3 ak (t ) = ∞ x(t ) = x(tª ) · š ξ ∞ ak e jkω 0t ∑ k =− ∞ ∫ T 0 x(t )dt = ∫ T 0 ∞ ak e jkω 0t dt = a0T ∑ k =− ∞ [email protected] 4 * 1· ª 3 à * ª · ªs - ∫ a1 T 0 x(t )e − jω 0 t T dt = ∫ e 0 − jω 0 t ∞ ak e jkω 0t dt = a1T ∑ k =− ∞ 1T a1 = ∫ x(t )e − jω 0t dt T0 1 ak = ∫ x(t )e − jkω 0t dt TT *ªη · ¾G 4 s FS hG ¾ª · (1)FS¾ h ª ·G (2)FSs * 6 · ª - à * xª (t· )¬ * ª y aks akª s· G kh * ¾ aks arg(ak )s ks * ª ·G ¾h [email protected] 5 * 1· ª 3 à * ª · ªs 3.2.2ª · h *’ * ª · ’1 h i FS s FS e jω 0 t − e − j ω 0 t x(t ) = sin ( ω 0t ) = 2j 1 a±1 = ± y ak = 0 2j y π t π π t x(t ) = 2cos + + sin y 2 3 3 s π t π cos + s 2 3 x(t ) = π t 4s sin s 3 [email protected] ∞ ak e jkω 0t ∑ k =− ∞ FSy FSy 6 6 * 1· ª 3 à * ª · ªs x(t ) 12 x(t ) = e π π j t+ 2 3 π j 3 =e e a± 3 = e *ª·š ã 2π π ω0 = = 12 6 ±j π 3 π jt 2 +e +e π π − j t+ 2 3 π −j 3 e π −j t 2 1 y a± 2 = ± y 2j + + e e π jt 3 π jt 3 −e 2j π −j t 3 −e 2j π −j t 3 = ∞ ak e jkω 0t ∑ k =− ∞ ak = 0 x(t ) = cos( t ) + cos( π t ) [email protected] 7 * 1· ª 3 à * ª · ªs - ( 1 jt x(t ) = cos(t ) + cos(π t ) = e + e − jt + e jπt + e − jπt 2 s s 2ª · * *s ’ x(t ) K p x(t )s * FS* ª·y ’ ) Kp x(t ) K p FSs FS [email protected] 8 * 1· ª 3 à * ª · ªs ∞ x(t ) = ∑a e k =− ∞ 1 ak = T ∫ T k x(t )e − jkω 0 t e = − jkω 0T 1 a0 = T õ0 2π ω0 = T jkω 0 t − jkω 0t T1 −T1 1 dt = T ∫ T2 −T 2 x(t )e − jkω 0t 1 dt = T ∫ e jkω 0T1 − e − jkω 0T1 sin( kω 0T1 ) = = j 2kπ kπ T1 −T1 e − jkω 0t dt ( k ≠ 0) 2T1 ∫T x(t )dt = T δ T (t ) FS [email protected] 9 * 1· ª 3 à * ª · ªs - δ T (t ) = 1 ak = T ∞ ∑a e k k =− ∞ ∫ T2 −T 2 jkω 0 t δ T (t )e 2π ω0 = T − jkω 0 t 1 dt = T ∫ T2 −T 2 δ (t )e 3.2.3ª · FS È*ÐY3 ’ñE − jkω 0 t 1 dt = T ª FS È · ’s [email protected] 10 * 1· ª 3 à * ª · ªs 1 s FS · L• ™ (1)s x(t ) ò 8 s (2)s x(t ) ò 8 x(t ) ò 8 x(t ) dt < ∞ s (3)y ∫ y 2 ˜ (1)¬ ª àš · (2)s x N (t ) = T FS Øš ઠ· x(t ) = x(t ) ò 8 ∞ ak e jkω 0t ∑ k =− ∞ N ak e jkω 0ts x N (tઠ)Øš *· ∑ x(t )s FS k =− N [email protected] 11 * 1· ª 3 à * ª · ªs lim x N (t ) = x(t ) (3) x N (t ) x(t ) y N →∞ N → ∞(å ª· š * ª · š 3( å FS x N· (tš )(å ª x(t ) * ª · FS ( šå ∀t ª · š (1)( å lim x N (t ) = x(t ) N →∞ lim lim ∫ x N (t ) − x(t ) dt = 0 ⇔ N →∞ ∫T x N (t ) − x(t ) dt = 0 2 (ª 2· )( šå N →∞ T * ª · å (š y x ( t) [email protected] 12 * 1· ª 3 à * ª · ªs x(t ) = ∞ ∑a e k =− ∞ k π T = 4 ω0 = 2 jkω 0 t sin( kω 0T1 ) sin( kπ 2) ak = = kπ kπ 2T1 1 a0 = = T 2 a±1 = 1 π a± 3 = − FS x N (t ) = 1 x0 (t ) = 2 1 3π a± 5 = 1 5π N ak e jkω 0t ∑ k =− N π 1 − jπ t 1 1 jπ t 1 2 2 2= + cos t x1 (t ) = e ++e 2π π 2π 2 [email protected] 13 * 1· ª 3 à * ª · ªs 12 π 2 3π x3 (t ) = + cos t − cos t 2π 2 3π 2 12 π 2 3π 2 5π x5 (t ) = + cos t − cos t + cos t 2π 2 3π 2 5π 2 lim ∫ x N (t ) − x(t ) dt N →∞ T =0 [email protected] 14 * 1· ª 3 à * ª · ªs - x N (t ) (1)y N → ∞y (2)y x N (t )8æš·ª N → ∞y x(t )8æš·ª* (3) x(t )8 ♠ • x(t ) x N (t )8æš·ª x(t ) lim x N (t ) ≠ x(t )8 ∗ ♠ • N →∞ [email protected] 15 * 1· ª 3 à * ª · ªs *ªH ·ê š x(t ) l • l• FS x N (t ) *ªH ·ê š x(t ) t = 1 + 4k y FSy x N (t )y y t ≠ 1 + 4ky êš·ª* Η N → ∞Hêš·ª* x N (t )Hêš·ª x(t ) x(t ) t = 1 + 4k [email protected] 16 * 1· ª 3 à * ª · ªs - x(t ) y FSy x N (t )Èæš·ª x(t ) x(t ) Èæš·ª* [email protected] 17 ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online